The New World challenge: Performance trends in wine production in major wine-exporting countries in the 2000s and their implications for the Australian wine industry - Euan Fleming; Stuart Mounter; Bligh Grant; Garry Richard Griffith; Renato Andrin Villano (Wine Economics and Policy, 2014)
Anderson, K., Nelgen, S., 2011. Global Wine Markets, 1961 to 2009: A Statistical Compendium. University of Adelaide Press, Adelaide publication of an index of revealed comparative advantage suggests that the Australian wine industry had come under increased competition from other "New world" producers in the first decade of this century. We examine this influence by comparing the transformation of winegrapes into wine volume and value in the 11 largest wine-exporting countries during the years, 2000-2009. Our focus is on the challenge issued by other New World producers from the Southern Hemisphere to Australian producers, and the continuing challenge to Old World global supremacy by New World producers and its response. Four performance measures are used this study. Two key trends are evident. First, all countries migrated to higher price points, albeit with differing degrees of success: slightly declining productivity in transforming winegrapes into wine output was overwhelmed by price/quality effects, leading to substantial gains in transforming winegrapes into wine value. Second, New World producers plus Portugal and Spain were much more successful in achieving gains in their export value proposition than they were in extracting value in their domestic markets. Results show that Australian wine producers had lost some of their competitive advantage during the 2000s as their pre-existing strategy dominated by the export of high-volume wines by large companies at low to medium price points, and their reliance on a reputation for reliable good quality for the price point was beginning to fail in the face of competition from both New World and Old World producers. Acknowledgement of this outcome has led to a good deal of introspection, and recognition of the need to promote the wine regions of Australia, based on higher-quality wines, and to select and promote quality indicators.
Keywords: 330; Australia; Competitiveness; Export; New World; Value proposition; Wine